Analysis and Study on Technique for Wireless Power Transfer depending upon Application Requirements - Nirvaan Sen (iJournals:International Journal of Software & Hardware Research in Engineering ISSN:2347-4890, 2021)
The purpose of our study is to design an efficient method for wireless power transfer (WPT) with high efficiency and low losses. In it we are working on a prototype based on mutual inductance and Tesla coil methods to calculate the parameters of wireless power transfer such as [i.e. Transmission efficiency, Transmission air Losses, Transmission Power losses, Transmission Distance, Impedance Losses]. The Research of wireless power transfer started in the year 1891 by Nicolas tesla father of wireless power transfer technology this journey continued till today having a lot of research opportunities and challenges in the field of WPT. We discuss the challenging issues with respect to various parameters of wireless power transfer like Cost of transmission.